# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}25 y^{\prime \prime }-20 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-24 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+9 y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+\frac {25 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime }-5 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 0
\] |
✓ |
✓ |
|
\[
{}m y^{\prime \prime }+k y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime }+5 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+p_{1} y^{\prime }+p_{2} y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-k y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-4 y^{\prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y^{\prime }+20 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+2 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+20 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 4 y
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-8 y^{\prime }+7 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}16 y^{\prime \prime }-8 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 a y^{\prime }+a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-5 x^{\prime }+6 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+5 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+3 x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-3 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime \prime } = -p^{2} \theta
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime \prime }-p^{2} \theta = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+12 y = 7 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}r^{\prime \prime }-a^{2} r = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -m^{2} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}e y^{\prime \prime } = P \left (-y+a \right )
\] |
✓ |
✓ |
|